Dentin Biomodification Potential Depends on Polyphenol Source. (April 2014) - Aguiar, T.R.; Vidal, C.M.P.; Phansalkar, R.S.; Todorova, I.; Napolitano, J.G.; McAlpine, J.B.; Chen, S.N.; Pauli, G.F.; Bedran-Russo, A.K.
Although proanthocyanidins (PACs) modify dentin, the effectiveness of different PAC sources and the correlation with their specific chemical composition are still unknown. This study describes the chemical profiling of natural PAC-rich extracts from 7 plants using ultra high pressure/performance liquid chromatography (UHPLC) to determine the overall composition of these extracts and, in parallel, comprehensively evaluate their effect on dentin properties. The total polyphenol content of the extracts was determined (as gallic acid equivalents) using Folin-Ciocalteau assays. Dentin biomodification was assessed by the modulus of elasticity, mass change, and resistance to enzymatic biodegradation. Extracts with a high polyphenol and PAC content from Vitis vinifera, Theobroma cacao, Camellia sinensis, and Pinus massoniana induced a significant increase in modulus of elasticity and mass. The UHPLC analysis showed the presence of multiple types of polyphenols, ranging from simple phenolic acids to oligomeric PACs and highly condensed tannins. Protective effect against enzymatic degradation was observed for all experimental groups; however, statistically significant differences were observed between plant extracts. The findings provide clear evidence that the dentin bioactivities of PACs are source dependent, resulting from a combination of concentration and specific chemical constitution of the complex PAC mixtures.